Long-term neuropsychologic outcome of pre-emptive mTOR inhibitor treatment in children with tuberous sclerosis complex (TSC) under 4 months of age (PROTECT), a two-arm, randomized, observer-blind, controlled phase IIb national multicentre clinical trial: study protocol - Driedger, Jan Henje; Schröter, Julian; Hertzberg, Christoph; Weschke, Bernhard; Kaindl, Angela M.; Lücke, Thomas; Thiels, Charlotte; Klotz, Kerstin A.; Fazeli, Walid; Rostásy, Kevin; Wiethoff-Ubrig, Lucia; Kaiser, Olaf; et al. (Orphanet journal of rare diseases, 2025)
Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder affecting multiple organ systems, with a prevalence of 1:6,760-1:13,520 live births in Germany. On the molecular level, TSC is caused by heterozygous loss-of-function variants in either of the genes TSC1 or TSC2, encoding the Tuberin-Hamartin complex, which acts as a critical upstream suppressor of the mammalian target of rapamycin (mTOR), a key signaling pathway controlling cellular growth and metabolism. Despite the therapeutic success of mTOR inhibition in treating TSC-associated manifestations, studies with mTOR inhibitors in children with TSC above two years of age have failed to demonstrate beneficial effects on disease-related neuropsychological deficits. It has thus been hypothesized, that the critical time window for mTOR inhibitors may lie in early infancy, before TSC-related symptoms such as early-onset epilepsy and infantile spasms as sign of disruptive brain maturation occur. No controlled prospective clinical trials have evaluated the effect of pre-symptomatic mTOR inhibitor therapy on neuropsychological manifestations in TSC patients under two years of age.